Development of a versatile copper‐responsive gene expression system in the plant‐pathogenic fungus Fusarium graminearum. (13th August 2021) - Kim, Sieun; Park, Jiyeun; Kim, Dohun; Choi, Soyoung; Moon, Heeji; Young Shin, Ji; Kim, Jung‐Eun; Son, Hokyoung
Abstract: Fusarium graminearum is an important plant‐pathogenic fungus that causes Fusarium head blight on wheat and barley, and ear rot on maize worldwide. This fungus has been widely used as a model organism to study various biological processes of plant‐pathogenic fungi because of its amenability to genetic manipulation and well‐established outcross system. Gene deletion and overexpression/constitutive expression of target genes are tools widely used to investigate the molecular mechanism underlying fungal development, virulence, and secondary metabolite production. However, for fine‐tuning gene expression and studying essential genes, a conditional gene expression system is necessary that enables repression or induction of gene expression by modifying external conditions. Until now, only a few conditional expression systems have been developed in plant‐pathogenic fungi. This study proposes a new and versatile conditional gene expression system in F . graminearum using the promoter of a copper‐responsive gene, designated F. graminearum copper‐responsive 1 ( FCR1 ). Transcript levels of FCR1 were found to be greatly affected by copper availability conditions. Moreover, the promoter ( PFCR1 ), 1 kb upstream of the FCR1 open reading frame, was sufficient to confer copper‐dependent gene expression. Replacement of a green fluorescent protein gene and FgENA5 promoter with a PFCR1 promoter clearly showed that PFCR1 could be used for fine‐tuning gene expression in this fungus. We also demonstrated the applicability of this conditional gene expression system to an essential gene study by replacing the promoter of FgIRE1, an essential gene of F . graminearum . This enabled the generation of FgIRE1 suppression mutants, which allowed functional characterization of the gene. This study reported the first conditional gene expression system in F . graminearum using both repression and induction. This system would be a convenient way to precisely control gene expression and will be used to determine the biological functions of various genes, including essential ones. Abstract : The FCR1 promoter ( PFCR1 ) could drive heterologous gene expression in a copper‐dependent manner and enabled functional characterization of an essential gene, FgIRE1, in Fusarium graminearum .